Team Performance Archetypes: Toward a New Conceptualization of Team Performance Over Time - Quigley, N.; Collins, C.; Gibson, C.; Parker, Sharon (2018)
© The Author(s) 2018. We examine the concept of team performance and propose a framework to understand patterns of change over time. Following a literature review on team performance (focusing on empirical articles published between 2007 and 2017) and drawing on Greek and Roman mythology, we identify five team performance trajectories: “Jupiter” (consistently high performing), “Neptune” (relatively steady, average performance), “Pluto” (low performing), “Icarus” (initially high performing, with a downward spiral), and “Odysseus” (initially low to midrange performing, with an upward spiral), which we refer to as “team performance archetypes.” We discuss how they might be used in conjunction with growth modeling methodology to help facilitate theory building and data collection/analysis with respect to team performance. In addition, we discuss the future research implications associated with using the archetypes to help conceptualize patterns of team performance over time.